Emotional Intelligence: why it can matter more than IQ - Goleman,Daniel (New Delhi Bloomsbury India, 2021)
A 25th anniversary edition of the number one, multi-million copy international bestseller that taught us how emotional intelligence is more important than IQ - 'a revolutionary, paradigm-shattering idea' (Harvard Business Review)Featuring a new introduction from the authorDoes IQ define our destiny? In his groundbreaking bestseller, Daniel Goleman argues that our view of human intelligence is far too narrow. It is not our IQ, but our emotional intelligence that plays a major role in thought, decision-making and individual success. Self-awareness, impulse control, persistence, motivation, empathy and social deftness: all are qualities that mark people who excel, whose relationships flourish, who can navigate difficult conversations, who become stars in the workplace. With new insights into the brain architecture underlying emotion and rationality, Goleman shows precisely how emotional intelligence can be nurtured and strengthened in all of us.
Keywords: IQ